Improved plant biomass production under low nitrogen conditions through conditional accumulation of the second messenger, guanosine tetraphosphate, in chloroplasts and mitochondria - Goto, Mina; Nemoto, Takanari; Sakoda, Kazuma; Sakurai, Atsushi; Imamura, Sousuke; Masuda, Shinji (Frontiers in Plant Science, 2025)
To enhance plant biomass production under low nitrogen conditions, we employed a method to artificially and temporarily accumulate the bacterial second messenger, guanosine tetraphosphate (ppGpp), to modify plastidial or mitochondrial metabolism. Specifically, we fused a chloroplast or mitochondrial transit-peptide to the N-terminus of the bacterial ppGpp synthase YjbM, which was conditionally expressed by an estrogen-inducible promoter in Arabidopsis. The resulting recombinant Arabidopsis plants exhibited estrogen-dependent ppGpp accumulation in chloroplasts or mitochondria and showed reduced fresh weight compared to wild type (WT) plants when grown on agar-solidified plates containing a certain amount of estrogen. This finding aligns with the previous study indicating that plastidial ppGpp levels can influence plant biomass production. When the recombinant plants were grown in the soil with estrogen and low nitrogen-containing water at specific time intervals, they exhibited greater fresh weight than WT plants. These results suggest that the conditional accumulation of ppGpp in not only chloroplasts, but also in mitochondria can lead to improved plant biomass production in soil with low nitrogen applications.